Navigating misinformation and political polarization of COVID-19: interviews with Milwaukee, Wisconsin county public health officials - Bates, Garrett; Titi, Mohammad; Dickson-Gomez, Julia; Young, Staci; Keval, Aliyah; Meurer, John (Frontiers in Public Health, 2023)
Introduction The spread of misinformation combined with the political polarization of the COVID-19 vaccine created major challenges for public health officials responding to the COVID pandemic and vaccine roll-out. The challenges public health officials faced when making safety recommendations and promoting the vaccine only exacerbated the already exhausting work conditions they experienced since the start of the pandemic. Combating misinformation while receiving inadequate political support led to burnout for many public health officials. As such, they had to adapt and develop new strategies for increasing vaccine acceptance and decreasing vaccine hesitancies. Method This study was conducted through qualitative interviews with seven Milwaukee County public health officials. This study aimed to determine how public health officials perceived misinformation and political polarization during the pandemic. Additionally, the study aimed to learn more about strategies county health officials used to combat misinformation while increasing vaccine uptake in their communities. Results Thematic analysis of the interviews identified three major challenges faced by public health officials in promoting vaccination: dissemination of misinformation in media, political polarization of COVID and its contribution to vaccine acceptance and COVID fatigue, and assessment of the risks associated with disease severity versus vaccine safety considering limited public health resources. Discussion Learning from public health officials allows us to better understand their perceptions of the extent of local vaccine hesitancies and their advice on how to counteract fears and misinformation and to promote COVID vaccine uptake. Political polarization of COVID and misinformation affected community vaccine acceptance and challenged local public health leadership.